Stress and debriefing – definitions and current controversies - Talarowska, Monika; Florkowski, Antoni; Wachowska, Katarzyna; Gałecki, Piotr (Current Problems of Psychiatry, 2011)
The phenomenon of stress is an extremely important issue for modern science. For many years, it has been subjected to numerous tests. There are three ways of understanding the term stress: stress understood as a stimulus, as a reaction of the body as well as a transaction that occurs between the unit and its surroundings. Finding effective ways to prevent the consequences of traumatic stress involves experts from various fields and is an important area of research. Particularly difficult issue is to help those who, in connection with their profession are vulnerable to negative consequences of stress (ER doctors, firemen, policemen, etc.). It seems important to use the methods which are characterized by proven effectiveness in research. One of currently undergoing intensive research method is created by Mitchell, and developed and modified by subsequent researchers, the Critical Incident Stress Debriefing (CISD). The authors present theoretical models of stress, and describe current models of debriefing which functions as one of the methods of crisis intervention. The article contains also an overview of research on a variety of applications and effectiveness of psychological debriefing. It summarizes the difficulties and restrictions on the use of this method.